A battery and its pole piece structure

By introducing a weakened transport layer and an active material layer into the electrode structure of the lithium-ion battery, a weak conductive coating is formed, which solves the problem of inconsistent lithium ions discharge speed at the edge of the electrode sheet, and improves the safety and performance uniformity of the battery.

CN222705526UActive Publication Date: 2025-04-01HUIZHOU LIWINON NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420564152.3
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-22
Publication Date
2025-04-01
Estimated Expiration
2034-03-22

AI Technical Summary

Technical Problem

Due to the inconsistent rates of lithium ions embedded and detachment of the electrode plate edges of existing lithium ion batteries, lithium ions are easily precipitated, causing lithium ions to be excreted at the edges of the electrode plate, affecting the performance and safety of the battery cell.

Method used

A battery electrode structure is adopted, including a metal layer, a weakened transport layer and an active material layer. The resistivity of the weakened transport layer is higher than that of the active material layer, forming a weak conductive coating to inhibit the removal rate of lithium ions.

Benefits of technology

It effectively suppresses the discharge speed of lithium ions at the edge of the electrode plate, prevents lithium ion from being excreted at the edge of the electrode plate, and improves the charging and discharging safety and performance uniformity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222705526U_ABST
    Figure CN222705526U_ABST
Patent Text Reader

Abstract

The utility model belongs to the technical field of batteries, and specifically relates to a battery pole piece structure, including a metal layer, a first end edge of the metal layer having a weakened transmission layer, a side of the weakened transmission layer away from the metal layer having an active material layer, and at least a part of the active material layer is embedded in the weakened transmission layer. The utility model can effectively suppress the release speed of lithium ions at the edge of the pole piece, thereby ensuring that the head and tail of the pole piece will not have the problem of lithium deposition. In addition, the utility model also discloses a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of batteries, and in particular relates to a battery and a pole piece structure thereof. Background Art

[0002] The head and tail of the existing lithium-ion battery are close to the edge of the battery. When the battery kinetic window is insufficient or the process affects the interface between the cathode and anode and the diaphragm, the edge effect of the battery affects the rate of lithium ion insertion and extraction at the edge of the battery cell and the main part. As a result, lithium ions are easily precipitated at the edge of the pole piece, causing lithium deposition at the edge of the battery cell pole piece, and causing the head and tail of the battery cell to be too thick, which in turn causes performance failure and safety risks of the battery cell. In the prior art, there is currently no effective improvement measure for this abnormality in the industry. It can be seen that how to make the battery pole piece structure have sufficient safety has become one of the important difficulties in battery structure design. Therefore, it is urgent to propose a new technical solution to solve the above problems. Utility Model Content

[0003] One of the purposes of the utility model is to address the deficiencies of the prior art and provide a battery electrode structure that can effectively suppress the release rate of lithium ions from the edge of the electrode, thereby ensuring that lithium deposition will not occur at the head and tail of the electrode.

[0004] In order to achieve the above purpose, the utility model adopts the following technical solutions:

[0005] A battery pole piece structure, comprising a metal layer, wherein a first end edge of the metal layer has a transmission weakening layer;

[0006] The side of the transmission weakening layer away from the metal layer has an active material layer;

[0007] At least a portion of the active material layer is embedded in the transmission weakening layer.

[0008] As an improvement to the pole piece structure of the battery of the utility model, the resistivity of the transmission weakening layer is at least 1.1 to 2 times the resistivity of the active material layer.

[0009] As an improvement to the pole piece structure of the battery of the utility model, the active material layer covers the surface of the weakened transmission layer and the metal layer to ensure that the area of ​​the metal layer excluding the weakened transmission layer, i.e., the main part of the metal layer, can quickly realize ion transmission.

[0010] As an improvement of the electrode structure of the battery of the utility model, the resistivity of the active material layer is 1.1×10 -2 Ω·m~1×10 2 Ω·m.

[0011] As an improvement of the pole piece structure of the battery of the utility model, the active material layer has a first part and a second part connected to each other, the first part and the weakened transmission layer are overlapped along the thickness direction of the pole piece structure to form a first overlapping area, the second part and the first overlapping area are arranged in parallel on the metal layer, the thickness difference between the second part and the first overlapping area is H, and the thickness of the weakened transmission layer is L 1 , the H and the L 1 Satisfy the relationship: 0≤H / L 1 ≤3. Within the above range, the thickness uniformity of the electrode can be ensured, thereby improving the charge and discharge uniformity of the battery.

[0012] As an improvement of the pole piece structure of the battery of the utility model, the width of the weakened transmission layer is W 1 , the thickness of the transmission weakening layer is L 1 , satisfying the relationship: 0.025≤L 1 / W 1 ≤0.05. Within this ratio range, the lithium ion release rate can be suppressed at the edge of the electrode to the best effect, effectively overcoming the safety problem of lithium deposition at the edge of the electrode and improving the charging and discharging safety of the battery.

[0013] As an improvement of the electrode structure of the battery of the utility model, the resistivity of the weakened transmission layer is ρ 1 The resistivity of the active material layer is ρ 2 The thickness of the active material layer located on the surface of the weakened transmission layer is L 2 , satisfying the relationship: 100≤(ρ 1 / ρ 2 )×L 2 ≤110. Within this ratio range, the lithium ion release rate can be suppressed at the edge of the electrode to the best effect, effectively overcoming the safety problem of lithium deposition at the edge of the electrode and improving the charging and discharging safety of the battery.

[0014] As an improvement of the pole piece structure of the battery of the utility model, the p 1 and the 2 Satisfies the relationship: 2≤ρ 1 / ρ 2 ≤20; i.e. 0.05≤ρ 2 / ρ 1 ≤0.5. Within this ratio range, effective regulation of the performance of reducing electron transport can be achieved.

[0015] As an improvement of the electrode structure of the battery of the utility model, the active material layer has an average particle size of d2 The thickness of the transmission weakening layer is L 1 , satisfying the relationship: 0.1≤L 1 / d 2 ≤0.4, by limiting the thickness of the weakened transport layer, the performance of reducing electron transport can be effectively regulated.

[0016] As an improvement of the pole piece structure of the battery of the utility model, the thickness of the active material layer embedded in the weakened transmission layer is d, and the d, the L 1 With the d 2 Satisfy the relationship: d <L 1 , 0.05≤d / d 2 ≤0.3, wherein this numerical range can prevent the active material layer from being embedded in the weakened transmission layer with too much thickness, so as to ensure that the active particles of the active material layer will not contact and scratch the metal layer. In addition, it is also necessary to prevent the active material layer from being embedded in the weakened transmission layer with too little thickness, so as to prevent the active material layer and the weakened transmission layer from having poor adhesion and easy delamination.

[0017] As an improvement of the pole piece structure of the battery of the utility model, the transmission weakening layer has an average particle size of d 1 The granules, the d 1 , the d and the L 1 Satisfy the relationship: d <d 1 <L 1 or 1 <d<L 1 The particles may be ceramic particles, which can increase the resistance of the weakened transmission layer, and the ceramic particles, as weakly conductive particles, have the effect of reducing electron transmission. The weakened transmission layer may be formed by a conductive agent and an average particle size of d 1 A mixture of ceramic particles.

[0018] As an improvement of the pole piece structure of the battery of the utility model, when the active material layer is in liquid state, it forms a contact angle of θ° with the surface of the solid weakening transmission layer, and the θ, the d and the L 1 Satisfy the relationship: 1≤θ×d / L 1 ≤15. Within the above range, it can ensure better bonding effect between the active material layer and the weakened transmission layer and the appearance of the electrode, thereby improving the charging and discharging safety of the battery.

[0019] As an improvement of the pole piece structure of the battery of the utility model, the d 2 is 10um~30um, the d 1is 0.5um~3um, d is 1um~3um, L 1 1um~4um, d 2 <L 2 , the H is 0-10um, the θ is 1.1-20. Within the above numerical ranges, the lithium ion escape rate can be suppressed at the edge of the electrode to the best effect, effectively overcoming the safety problem of lithium deposition at the edge of the electrode, while ensuring the uniformity of the electrode and improving the charging and discharging safety of the battery.

[0020] The second purpose of the utility model is to provide a battery, comprising the above-mentioned pole piece structure.

[0021] The beneficial effects of the utility model are as follows: the pole piece structure of the battery of the utility model includes a metal layer, the edge of the first end of the metal layer has a weakened transmission layer, the side of the weakened transmission layer away from the metal layer has an active material layer, at least part of the active material layer is embedded in the weakened transmission layer, wherein the weakened transmission layer arranged between the metal layer and the active material layer has a certain resistance value to form a weak conductive coating, so that the weakened transmission layer, which has a slightly weaker conductivity than the active material layer, can reduce the transmission rate of electrons and inhibit the release rate of lithium ions at the edge of the pole piece, which can effectively solve the safety problem of lithium deposition at the edge of the pole piece and ensure that lithium deposition will not occur at the head and tail of the pole piece. At least part of the active material layer is embedded in the weakened transmission layer, which can improve the bonding strength between the active material layer and the weakened transmission layer, and improve the safety and quality of the pole piece. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is one of the structural schematic diagrams of the metal layer, the transmission weakening layer and the active material layer of the utility model.

[0023] Figure 2 This is the second structural schematic diagram of the metal layer, the transmission weakening layer and the active material layer of the utility model.

[0024] Figure 3 It is a schematic diagram of the structure of the pole piece of the utility model.

[0025] Figure 4 It is a schematic diagram of reducing the ion transmission difference between the transport layer and the active material layer of the present invention.

[0026] Wherein: 1, metal layer; 2, weakened transmission layer; 21, particle body; 3, active material layer; 3a, first part; 3b, second part; 31, active particles; L 1 , reduce the thickness of the transmission layer; L 2, the thickness of the active material layer located on the surface of the weakened transmission layer; d, the thickness of the active material layer embedded in the weakened transmission layer; H, the difference in thickness between the second part of the active material layer and the first overlapping area formed in the pole piece structure; T, the thickness direction of the pole piece structure. DETAILED DESCRIPTION

[0027] If certain words are used in the specification and claims to refer to specific components, those skilled in the art should understand that manufacturers may use different terms to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but rather use differences in components' functions as the criteria for distinction. For example, "including" mentioned throughout the specification and claims is an open term and should be interpreted as "including but not limited to".

[0028] The following is combined with Figures 1 to 4 The utility model is further described in detail with specific embodiments, but is not intended to limit the utility model.

[0029] A battery electrode structure, see Figures 1 to 3 , including a metal layer 1, a first end edge of the metal layer 1 having a weakened transmission layer 2, a side of the weakened transmission layer 2 away from the metal layer 1 having an active material layer 3, at least a portion of the active material layer 3 is embedded in the weakened transmission layer 2, wherein the weakened transmission layer 2 arranged between the metal layer 1 and the active material layer 3 has a certain resistance value to form a weakly conductive coating, and the resistivity of the weakened transmission layer 2 is greater than the resistivity of the active material layer 3, so that the weakened transmission layer 2, which is slightly weaker in conductivity than the active material layer 3, can reduce the transmission rate of electrons and inhibit the release rate of lithium ions at the edge of the electrode, which can effectively solve the safety problem of lithium deposition at the edge of the electrode and ensure that lithium deposition does not occur at the head and tail of the electrode. Preferably, the resistivity of the weakened transmission layer 2 is at least 1.1 to 2 times the resistivity of the active material layer 3.

[0030] Preferably, the active material layer 3 covers the surface of the weakened transmission layer 2 and the metal layer 1, and the resistivity of the active material layer 3 is 1.1×10 -2 Ω·m~1×10 2 Ω·m.

[0031] Preferably, the resistivity of the weakened transmission layer 2 is p 1 The resistivity of the active material layer 3 is ρ 2 The thickness of the active material layer 3 located on the surface of the weakened transmission layer 2 is L 2 , satisfying the relationship: 100≤(ρ 1 / ρ 2 )×L 2 ≤110, 0.05≤ρ 2 / ρ 1≤0.5.

[0032] Preferably, 1 and ρ 2 Satisfies the relationship: 2≤ρ 1 / ρ 2 ≤2.5、2.5≤ρ 1 / ρ 2 ≤3, 3≤ρ 1 / ρ 2 ≤3.5、3.5≤ρ 1 / ρ 2 ≤4, 4≤ρ 1 / ρ 2 ≤7.5、7.5≤ρ 1 / ρ 2 ≤10.5、10.5≤ρ 1 / ρ 2 ≤16.5 or 16.5≤ρ 1 / ρ 2 ≤20.

[0033] Preferably, the thickness of the active material layer 3 embedded in the weakened transmission layer 2 is d, and the active material layer 3 has an average particle size of d 2 The active particles 31 satisfy the relationship: 0.05≤d / d 2 ≤0.1, 0.1≤d / d 2 ≤0.15, 0.15≤d / d 2 ≤0.2, 0.2≤d / d 2 ≤0.25 or 0.25≤d / d 2 ≤0.3.

[0034] Preferably, the width of the weakened transmission layer 2 is W 1 , the thickness of the weakened transmission layer 2 is L 1 , W 1 With L 1 Satisfy the relationship: 0.005≤L 1 / W 1 ≤0.015、0.015≤L 1 / W 1 ≤0.025、0.025≤L 1 / W 1 ≤0.03, 0.03≤L 1 / W 1 ≤0.035、0.035≤L 1 / W 1 ≤0.04, 0.04≤L 1 / W 1 ≤0.045 or 0.045≤L 1 / W 1 ≤0.05.

[0035] Preferably, the active material layer 3 has a first part 3a and a second part 3b connected to each other, the first part 3a and the weakened transmission layer 2 are overlapped along the thickness direction T of the pole piece structure to form a first overlapping area, the second part 3b and the first overlapping area are arranged in parallel on the metal layer 1, the thickness difference between the second part 3b of the active material layer 3 and the first overlapping area formed in the pole piece structure is H, and the thickness value of the weakened transmission layer 2 is L 1 , satisfying the relationship: 0≤H / L 1 ≤1, 1≤H / L 1 ≤2, 2≤H / L 1 ≤3, H is the thickness difference between the first overlapping area and the second part 3b on a single side of the pole piece.

[0036] Preferably, L 1 , d and d 2 Satisfy the relationship: d <L 1 , 0.1≤L 1 / d 2 ≤0.4. Among them, L 1 and d 2 Satisfy the relationship: 0.1≤L 1 / d 2 ≤0.15、0.15≤L 1 / d 2 ≤0.17, 0.17≤L 1 / d 2 ≤0.195、0.195≤L 1 / d 2 ≤0.25、0.25≤L 1 / d 2 ≤0.3, 0.3≤L 1 L 1 / d 2 ≤0.35 or 0.35≤L 1 / d 2 ≤0.4.

[0037] Preferably, the transmission weakening layer 2 has an average particle size of d 1 The particles 21,d 1 , d and L 1 Satisfy the relationship: d <d 1 <L 1 or 1 <d<L 1 .

[0038] Preferably, when the active material layer 3 is in liquid state, it forms a contact angle of θ° with the surface of the solid weakening transmission layer 2, that is, the slurry of the active material layer 3 is dropped onto the surface of the weakening transmission layer 2 to form a contact angle of θ°. The contact angle is formed by the contact between the liquid and the solid before drying, and is actually the interface angle formed by the active material layer 3 in liquid state and the weakening transmission layer 2 in solid state. The solid content of the liquid active material layer 3 is 45-55%; the weight loss rate of the solid weakening transmission layer 2 is ≤1%.

[0039] More preferably, θ, d and L 1 Satisfy the relationship: 1≤θ×d / L 1 ≤5, 5≤θ×d / L 1 ≤10、10≤θ×d / L 1 ≤15, wherein the contact angle value can be 1.1°~20°.

[0040] Preferably, the metal layer 1 has two opposite first end edges, two transmission weakening layers 2 are relatively arranged on the same side of the metal layer 1, there are four transmission weakening layers 2 on the front and back sides of the metal layer 1, and there is an active material layer 3 on the front and back sides of the metal layer 1 respectively.

[0041] Among them, the resistance value test method of the coating can be tested by a four-probe method; the contact angle test method is a sessile drop method, and the test is completed using an optical contact angle meter.

[0042] In addition, the utility model also provides a battery, including a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet of the battery is the above-mentioned electrode sheet structure containing a metal layer 1, a weakened transmission layer 2 and an active material layer 3. The battery can be a lithium ion battery, a sodium ion battery, a magnesium ion battery, etc.

[0043] Example 1

[0044] Positive electrode: see Figures 1 to 3 , comprising a metal layer 1, a weakened transmission layer 2 and an active material layer 3, wherein the metal layer 1 is an aluminum current collector, and a weakly conductive material is first coated on the aluminum current collector, and the weakly conductive material can be formed by a conductive agent and an average particle size of d 1 Ceramic particles are mixed, d 1 The thickness of the weak conductive material is 1.5um, and the position where the weak conductive material is applied corresponds to the head and tail of the battery cell, that is, the weakened transmission layer 2 is coated on the edge of the first end of the metal layer 1 to obtain a weak conductive current collector, and then the positive electrode active material, the conductive agent acetylene black, the conductive carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are fully and evenly dispersed in the N-methylpyrrolidone solvent system in a weight ratio of 97.8:0.6:0.4:1.2 to obtain a positive electrode active material slurry, and the positive electrode active material slurry is the active material layer 3, wherein the positive electrode active material can be LiCoO2 、LiNiO 2 、LiVO 2 、LiCrO 2 、LiMn 2 O 4 、LiCoMnO 4 , Li 2 NiMn 3 O 8 、LiNi 0.5 Mn 1.5 O 4 、LiCoPO 4 、LiMnPO 4 、LiFePO 4 、LiNiPO 4 、LiCoFSO 4 , CuS 2 , FeS 2 、MoS 2 、NiS、TiS 2 One or more of the above, the active particles 31 are a mixture of positive electrode active material, conductive agent acetylene black, and conductive carbon nanotubes. Finally, the positive electrode active material slurry is coated on the weakly conductive current collector. The part of the positive electrode active material slurry superimposed on the weakened transmission layer 2 is the first part 3a, and the part of the positive electrode active material slurry not superimposed on the weakened transmission layer 2 is the second part 3b, and then cold pressed into strips to obtain the positive electrode sheet.

[0045] Negative electrode sheet: negative electrode active material, sodium carboxymethyl cellulose and styrene-butadiene rubber (SBR) emulsion are mixed in a weight ratio of 97.4:1.3:1.3 to prepare negative electrode active material slurry. The negative electrode active material can be a silicon-carbon material; the active material slurry is coated on a copper current collector to obtain an active material layer, and then cold pressed and striped to obtain a negative electrode sheet.

[0046] Isolation film: The PE surface is coated with a ceramic mixture as an isolation film.

[0047] Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) were mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF 6 It is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0048] Preparation of a full battery: The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0049] Among them, the resistivity ρ of the weakened transmission layer 2 in the positive electrode plate is 1is 0.4Ω·m, and the resistivity ρ of the active material layer 3 2 is 0.16Ω·m, the thickness d of the first portion 3a of the active material layer 3 embedded in the weakened transmission layer 2 is 2.1um, and the thickness L of the weakened transmission layer 2 is 1 is 2.7 μm, and the thickness L of the first portion 3 a of the active material layer 3 is 2 The average particle size d of the active particles 31 is 43 μm. 2 The thickness difference H between the first overlapping area formed by the weakened transmission layer 2 and the first part 3a of the active material layer 3 and the adjacent second part 3b of the active material layer 3 in the electrode structure is 4.6um. The slurry of the active material layer 3 is dripped onto the surface of the weakened transmission layer 2 to form a contact angle of θ°=5°. By adjusting ρ 1 , 2 ,d,L 1 , L 2 and d 2 The following Examples 2 to 3 and Comparative Examples 1 to 5 were obtained, and the specific parameters are shown in Table 1. Moreover, H, θ, and ρ in Example 1 and Comparative Examples 1 and 4 are 1 , L 1 , d and d 2 are the same, only ρ 2 and L 2 Different; H, θ, ρ in Example 1 and Comparative Example 2 1 , 2 , L 1 and d 2 are the same, only d and L 2 Different; H and θ in Example 1 and Example 2 are the same; d in Example 2 and Comparative Example 3 2 Same as H, θ, ρ in Comparative Example 3 1 , L 1 and d are all 0; H, θ, d and d in Example 2 and Comparative Example 5 2 are the same, only ρ 1 , 2 , L 1 and L 2 Different; H, θ and L in Example 1, Example 3 and Comparative Example 5 1 are the same.

[0050]

[0051]

[0052] Table 1

[0053] Performance tests were conducted on Examples 1 to 3 and Comparative Examples 1 to 5. The charging window is the maximum rate at which the cell does not deposit lithium after the cell interface is disassembled at the cut-off voltage when the cell is directly charged under 3.0C, 3.5C, 4.0C, 4.5C, 5.0C, and 5.5C conditions. The charging time is the time corresponding to full charging under 5C and 3C cycle conditions. The lithium deposition windows of Examples 1 to 3 and Comparative Examples 1 to 5 are obtained as shown in Table 2 below.

[0054] Lithium Separation Window 3C charging time 5C charging time Example 1 5C 25min 20min Example 2 4C 38min 30min Example 3 5C 26min 21min Comparative Example 1 5C 29min 25min Comparative Example 2 4C 22min 17min Comparative Example 3 3C 35min 30min Comparative Example 4 4.5C 23min 19min Comparative Example 5 4C 43min 33min

[0055] Table 2

[0056] When there is no weak conductive layer or when the active material layer particles penetrate the weak conductive layer and directly contact the foil, the electron transmission rate cannot be effectively suppressed, resulting in an accelerated rate of lithium ion release, resulting in lithium precipitation. Figure 4 , weakening the transmission layer 2 effectively reduces the electron transmission rate and inhibits the release rate of lithium ions. From the above table, it can be seen that when the resistivity ratio of the weak conductive coating to the active material layer does not match the thickness of the electrode, it significantly affects the performance of the battery cell, such as (ρ 1 / ρ 2 )×L 2 When ρ<100, the electron transfer rate cannot be effectively suppressed, resulting in an accelerated rate of lithium ion release, resulting in lithium precipitation. 1 / ρ 2 )×L 2 When >110, the lithium ion insertion and extraction rate is too slow and the charging time increases.

[0057] Therefore, the key to this solution is to control the relationship between the thickness of the weak conductive coating and the average particle size of the active material layer, as well as the relationship between the resistivity of the weak conductive coating and the resistivity and thickness of the active material layer, that is, to control the resistivity ρ of the weakened transmission layer 2 in the pole piece. 1 , the resistivity ρ of the active material layer 3 2 , the active material layer 3 is embedded in the weakened transmission layer 2 by a thickness d, and the weakened transmission layer 2 has a thickness L 1 , the thickness L of the active material layer 3 located on the surface of the weakened transport layer 2 2 and the average particle size d of the active particles 31 2 , so that 100≤(ρ 1 / ρ 2 )×L 2 ≤110,2ρ 2 ≤ρ 1 ≤20ρ 2 , 0.05d 2 ≤d≤0.3d 2 , 0.1d 2 ≤L 1 ≤0.4d2 And d<L 1 ; d is 1um~3um; L 1 1um~4um; d 2 Under these conditions, the weakly conductive coating reduces the electron transmission rate, inhibits the escape rate of lithium ions, and ensures that the active material layer particles will not pierce the weakly conductive layer, so as not to directly contact the foil and cause the effect of reducing the electron transmission rate to fail.

[0058] On the other hand, the present invention also obtains Examples 4 to 6 by changing only the value of θ on the basis of Examples 1 to 3, obtains Comparative Examples 6 to 9 by changing only θ on the basis of Comparative Examples 1 to 4, obtains Comparative Example 10 by changing only the value of d on the basis of Example 4, and obtains Comparative Example 10 by changing only the value of L on the basis of Example 4. 1 The value of comparative example 11 is obtained to explore the degree of the contact angle and the thickness L of the weakened transmission layer 2 1 , the relationship between the thickness d of the active material layer 3 embedded in the weakened transport layer 2 is used to obtain the design parameters in Table 3 and the difference in Poweloss under the 4C cycle conditions in Table 4.

[0059] <![CDATA[L 1 (one)]]> d(um) θ(°) Example 4 2.7 2.1 3 Example 5 3.8 1.6 20 Example 6 2.7 1.8 10 Comparative Example 6 2.7 2.1 30 Comparative Example 7 2.7 2.9 15 Comparative Example 8 0 0 180 Comparative Example 9 2.7 2.1 24 Comparative Example 10 2.7 0.7 3 Comparative Example 11 7 2.1 3

[0060] Table 3

[0061] Powerloss refers to the difference between the capacity ratio of standard charge and discharge per 100-cycle node and the capacity ratio of standard charge and discharge in the adjacent cycle number cycle, which is used to characterize the polarization of the battery cell. The larger the powerloss, the greater the polarization of the battery cell, and vice versa. The following results are obtained by comparing Examples 4 to 6 with Comparative Examples 6 to 11.

[0062]

[0063]

[0064] Table 4

[0065] It can be seen from the table that when the thickness d of the active material layer 3 embedded in the weak conductive coating is reduced, the thickness L of the transmission layer 2 is reduced. 1 When the ratio of the active material layer 3 slurry dropped onto the weakened transmission layer 2 shows an unmatched relationship with the contact angle of the surface formation value of θ°, that is, θ×d / L 1 Too large or too small will obviously affect the performance of the battery. When 1≤θ×d / L 1 When ≤15, there is a better bonding effect and pole piece appearance between the active material layer 3 and the weakened transmission layer 2. As the cycle progresses, the pole piece is in a stable state, and the polarization grows slowly. θ×d / L 1 <1 or 15<θ×d / L 1When the active material layer 3 and the weakened transmission layer 2 are used, the bonding effect between the active material layer 3 and the weakened transmission layer 2 is weak. As the cycle proceeds, the active material layer 3 and the weakened transmission layer 2 begin to separate, resulting in a significant increase in the polarization of the battery cell, affecting the cycle performance of the battery cell.

[0066] Finally, this solution also obtains Example 7 by changing only the value of H on the basis of Example 1, and by changing only H and L on the basis of Example 7. 1 Examples 8 to 9 and comparative examples 12 to 14 are obtained to prove the influence of such a pole piece structure on the uniformity of charge and discharge, that is, to further explore the relationship between H and the thickness value L of the weakened transmission layer 2. 1 The design parameters of Table 5 are obtained from the relationship, and the difference in capacity retention under the 5C cycle standard condition is obtained from such parameters in Table 6. At the same time, such a test can meet the single variable principle. Compared with Example 1 in Table 1, the variables of Examples 8 to 9 and Comparative Examples 12 to 14 are only H and L. 1 .

[0067]

[0068]

[0069] Table 5

[0070] The following results were obtained by comparing Examples 7 to 9 with Comparative Examples 12 to 14.

[0071]

[0072] Table 6

[0073] It can be seen from the table that when H is equal to the thickness L of the weakened transmission layer 2 1 When the match is not made, the performance of the battery cell will be significantly affected. When 3≤H / L 1 When the thickness uniformity of the electrode sheet is poor, there is local polarization inconsistency, which leads to poor charge and discharge uniformity, thus affecting the cycle retention rate. It can be seen that H is related to the thickness value L of the weakened transmission layer 2. 1 Satisfy the relationship: 0≤H / L 1 When ≤3, within the above range, the uniformity of charge and discharge of the electrode can be guaranteed, thereby improving the corresponding electrical performance of the battery.

[0074] According to the disclosure and teaching of the above description, those skilled in the art to which the utility model belongs can also change and modify the above implementation. Therefore, the utility model is not limited to the above specific implementation, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the utility model belongs to the protection scope of the utility model. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the utility model.

Claims

1. A battery pole piece structure, characterized in that: Comprising: A metal layer (1), a first end edge of the metal layer (1) having a weakened transmission layer (2); One side of the weakened transmission layer (2) away from the metal layer (1) has an active material layer (3); At least a part of the active material layer (3) is embedded in the weakened transmission layer (2).

2. The battery pole piece structure according to claim 1, characterized in that: The active material layer (3) covers the surfaces of the weakened transmission layer (2) and the metal layer (1), and the resistivity of the active material layer (3) is 1.1×10 -2 Ω·m~1×10 2 Ω·m.

3. The battery pole piece structure according to claim 1 or 2, characterized in that: The active material layer (3) has a first part (3a) and a second part (3b) connected to each other. The first part (3a) and the weakened transmission layer (2) are stacked in the thickness direction of the electrode structure to form a first stacking region. The second part (3b) is arranged side by side with the first stacking region on the metal layer (1). The thickness difference between the second part (3b) and the first stacking region is H, and the thickness of the weakened transmission layer (2) is L1. The H and the L1 satisfy the relationship: 0 ≤ H / L1 ≤ 3.

4. The battery pole piece structure according to claim 1 or 2, characterized in that: The width of the weakened transmission layer (2) is W1, and the thickness of the weakened transmission layer (2) is L1, satisfying the relationship: 0.005 ≤ L1 / W1 ≤ 0.

05.

5. The battery pole piece structure according to claim 1 or 2, characterized in that: The resistivity of the weakened transmission layer (2) is ρ1, and the resistivity of the active material layer (3) is ρ2. The resistivity of the weakened transmission layer (2) is at least 1.1 to 2 times the resistivity of the active material layer (3).

6. The battery pole piece structure according to claim 5, characterized in that: The thickness of the active material layer (3) on the surface of the weakened transmission layer (2) is L2, satisfying the relationship: 100 ≤ (ρ1 / ρ2) × L2 ≤ 110, 2 ≤ ρ1 / ρ2 ≤ 20.

7. The pole piece structure of a battery as claimed in claim 1 or 2, characterized in that: The active material layer (3) has active particles (31) with an average particle size of d2, and the thickness of the weakened transmission layer (2) is L1, satisfying the relationship: 0.1 ≤ L1 / d2 ≤ 0.

4.

8. The battery pole piece structure according to claim 7, characterized in that: The thickness of the active material layer (3) embedded in the weakened transmission layer (2) is d. The d, the L1, and the d2 satisfy the relationship: d < L1, 0.05 ≤ d / d2 ≤ 0.

3.

9. The battery pole piece structure according to claim 8, characterized in that: The weakened transmission layer (2) has particulate bodies (21) with an average particle size of d1. The d1, the d, and the L1 satisfy the relationship: d < d1 < L1 or d1 < d < L1.

10. The battery pole piece structure according to claim 8, characterized in that: When the active material layer (3) is in a liquid state, it forms a contact angle of θ° with the surface of the solid weakened transmission layer (2). The θ, the d, and the L1 satisfy the relationship: 1 ≤ θ × d / L1 ≤ 15.

11. A battery, characterized in that: Including the electrode structure according to any one of claims 1 to 10.